A Portrait of Tri Kaya Parisudha in Cingkreman (Hofstede's Study of Cultural Dimensions) - Eka Putri Suryantari; Ni Luh Putu Wiagustini; I Putu Sudana; Ni Ketut Rasmini (Mudra Jurnal Seni Budaya, 2024)
Cultural practices in society are greatly influenced by the extent to which they are able to provide benefits to those who practice them. One of the cultural practices that is still found in the heritage region of the city of Denpasar is called cingkreman. This is a culture-based and family-based financial planning and savings system. Cingkreman is based on an agreement between individuals to join a cingkreman group (sekaa). The period of participation for one period corresponds to the cycle of the Galungan holidays, namely 210 days. The novelty of this research is to bring to the surface the cultural practices that exist in society so that efforts can be made to preserve the tradition of cingkreman. This is qualitative research with an interpretive paradigm that uses an ethnomethodological approach. The aim of this research is to find out how the concept of Tri Kaya Parisudha (moral teaching about personal behavior) is applied to cingkreman and how this practice continues to exist in the midst of society. The data were collected through interviews and focus group discussions (FGDs). The research results show that the Tri Kaya Parisudha concept is practiced in the cingkreman system. The behavior of the members and coordinators of a sekaa, as reflected in the themes resulting from the stages of Garfinkel's analysis, reflects kayika parisudha (good acts), wacika parisudha (good speech), and manacika parisudha (good thought). The foundation of behavior based on these three noble attitudes of Tri Kaya Parisudha is able to produce cultural values which cause the practice of cingkreman to provide benefits to its practitioners. The benefits felt by these actors mean that cingkreman will continue to be practiced, and this is one of the reasons why the carrying out of cingkreman persists amidst technological advances which are slowly eroding existing cultural practices in society. Hofstede's cultural dimensions that are found in the practice of cingkreman include uncertainty avoidance, collectivity, and femininity. The dimension of power differences is not found because, in the practice of cingkreman, there are no differences between the participants in the social strata. Everyone has the same right to join the cingkreman group.